Influence of humic acid on radium adsorption by coir pith in aqueous solution - Zalina Laili,; Muhamad Samudi Yasir, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This study examines the influence of humic acids (HA) on adsorption of radium (Ra) ions onto coir pith (CP) in aqueous solution. The adsorption behaviours of Ra ions onto CP under the influence of HA in aqueous solution were investigated in the series of batch mode adsorption experiments. The effects of various experimental conditions such as pH, contact time, adsorbent dosage and initial concentration of Ra ions have been studied. The results revealed that the presence of HA in aqueous solution enhanced the adsorption of Ra ions onto CP. The adsorption results showed that the percentage of Ra adsorbed was increased with an increase in the pH or alkalinity of aqueous solutions. Time dependence of the batch studies showed that a contact time of one day was sufficient to reach equilibrium. The result also showed that there was no significant difference on the effect of adsorbent dose on adsorption of radium onto CP. It was shown that the equilibrium data could be fitted by Freundlich equation.